Esophageal Rupture as a Primary Manifestation in Eosinophilic Esophagitis. (11th May 2014) - Vernon, Natalia; Mohananey, Divyanshu; Ghetmiri, Ehsan; Ghaffari, Gisoo
Abstract : Eosinophilic esophagitis (EoE) is a chronic inflammatory process characterized by symptoms of esophageal dysfunction and, histologically, by eosinophilic infiltration of the esophagus. In adults, it commonly presents with dysphagia, food impaction, and chest or abdominal pain. Chronic inflammation can lead to diffuse narrowing of the esophageal lumen which may cause food impaction. Endoscopic procedures to relieve food impaction may lead to complications such as esophageal perforation due to the friability of the esophageal mucosa. Spontaneous transmural esophageal rupture, also known as Boerhaave's syndrome, as a primary manifestation of EoE is rare. In this paper, we present two adult patients who presented with esophageal perforation as the initial manifestation of EoE. This rare complication of EoE has been documented in 13 other reports (11 adults, 2 children) and only 1 of the patients had been previously diagnosed with EoE. A history of dysphagia was present in 1 of our patients and in the majority of previously documented patients. Esophageal perforation is a potentially severe complication of EoE. Patients with a history of dysphagia and patients with spontaneous esophageal perforation should warrant an evaluation for EoE.